1993
DOI: 10.1136/jcp.46.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Xanthogranulomatous gastritis: association with xanthogranulomatous cholecystitis.

Abstract: ResultsThe gastrectomy specimen consisted of a 12 x 10 cm segment of stomach with irregular mucosal and serosal surfaces. On sectioning of the antropyloric region, a firm, yellowish-white

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…One case of xanthogranulomatous infiltration of the gastric wall has been described [5]. As previously reported by others [4,6,7], in patients with XGC there is a high incidence of complications such as gallbladder perforation, fistulation (to the skin, the colon and the duodenum), hepatic abscesses and gallbladder strictures.…”
Section: Discussionmentioning
confidence: 72%
“…One case of xanthogranulomatous infiltration of the gastric wall has been described [5]. As previously reported by others [4,6,7], in patients with XGC there is a high incidence of complications such as gallbladder perforation, fistulation (to the skin, the colon and the duodenum), hepatic abscesses and gallbladder strictures.…”
Section: Discussionmentioning
confidence: 72%
“…Although no studies have described a correlation between xanthogranulomatous gastritis and previous gastric surgery, the pathogenesis in the present case may be associated with the response following the previous surgery, as the tumor was located at the previous suture line. In addition, Guarino et al (11) suggested the potential correlation of bile …”
Section: Discussionmentioning
confidence: 99%
“…However, rare cases of xanthogranulomatous inflammation have additionally been reported in other organs, including the stomach, colon, pancreas and uterus (3-6). The occurrence of xanthogranuloma of the stomach is rare, and only a few cases have been reported to date (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). To the best of our knowledge, this is the first reported case of xanthogranulomatous gastritis in the remnant stomach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goblet cell metaplasia in Barrett's esophagus and stomach show a smooth, bland nucleus not deformed by a vacuole. Xanthelesma of the stomach, xanthogranulomatous 8 and granulomatous gastritis, 7 foreign body granuloma, inflammatory pseudotumor, muciphages, melanosis coli, storage disorders (such as polyvinyl pyrollidine disease 9 ) and inflammatory bowel disease all contain cells with benign histiocytes.…”
mentioning
confidence: 99%